2014
DOI: 10.1080/1046669x.2013.831014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ownership in Managing Interfirm Opportunism: A Dyadic Study

Abstract: We extend research on transaction cost theory that shows that vertical integration enables firms to protect their investments in exchange relationships better than market mechanisms. However, extant research finds ownership to exacerbate, rather than limit, exchange partner opportunism. Hence, the purpose of this study is to investigate conditions under which ownership can be effective for constraining an exchange partner's opportunism. Using matched dyadic data for 296 hotel brands, we conduct multilevel hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 75 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…This suggests that ownership does not provide enough incentive intensity to deal with situations, such as those found in 5-Star hotels, in which preventing managerial shirking is key. This finding is consistent with the results of Brown et al (2014), who found that, in the presence of high monitoring difficulties, chain-owned hotels face more problems of management opportunism. However, it is contrary to the results of Andreu et al (2020) and Kruesi et al (2018) that support the opposite hypothesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that ownership does not provide enough incentive intensity to deal with situations, such as those found in 5-Star hotels, in which preventing managerial shirking is key. This finding is consistent with the results of Brown et al (2014), who found that, in the presence of high monitoring difficulties, chain-owned hotels face more problems of management opportunism. However, it is contrary to the results of Andreu et al (2020) and Kruesi et al (2018) that support the opposite hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…3 In line with these arguments and focusing on the hotel industry, previous research has related the adoption of franchise agreements with the difficulty of monitoring the hotel manager (Alon et al, 2012; Fladmoe-Lindquist & Jacque, 1995; Norton, 1988). In the same vein, the study by Brown et al (2014) reveals that when monitoring a hotel is difficult, chain headquarters face higher opportunism from chain-owned facilities.…”
Section: Governance Mechanisms and Hotel Performancementioning
confidence: 99%
“…In this way, SCT is consistent with relational exchange theory, which is based on the premise that a socialization process takes place when firms develop relationships. These relationships over time lead to shared goals and reduce opportunism within and between firm relationships (Brown et al , 2014).…”
Section: Social Capital Theory In the Context Of New Mediamentioning
confidence: 99%
“…Both opportunism and uncertainty are shown to influence a range of outcomes such as service quality and costs in an outsourcing arrangement (Wathne & Heide, 2000). At the same time, TCA scholars (Brown, Krishen, & Dev, 2014;Rindfleisch & Heide, 1997) examined various antecedents of opportunism in inter-firm relationships but did not incorporate supplier firm characteristics as indicators of pre-contract opportunism.…”
Section: Introductionmentioning
confidence: 99%